U‐Pb SIMS ages of Apollo 14 zircon: Identifying distinct magmatic episodes. (12th June 2019) - Thiessen, F.; Nemchin, A. A.; Snape, J. F.; Whitehouse, M. J.
Abstract: U‐Pb ages of zircon in four different Apollo 14 breccias (14305, 14306, 14314, and 14321) were obtained by secondary ion mass spectrometry. Some of the analyzed grains occur as cogenetic, poikilitic zircon grains in lithic clasts, revealing magmatic events at 4286 Ma, 4200–4220 Ma, and 4150 Ma. The age distribution of the crystal clasts in the breccias exhibits a minor peak at 4210 Ma, which can be attributed to a magmatic event, as recorded in zircon grains located in noritic clasts. An age peak at 4335 Ma is present in all four breccias, as well as zircon grains from different Apollo landing sites, enhancing the confidence that these grains recorded a global zircon‐forming event. The overall age distribution among the four breccias exhibits minor differences between the breccias collected farther away from the Cone Crater and the ones collected within the continuous ejecta blanket of the Cone Crater. A granular zircon grain yielded a 207 Pb/ 206 Pb age of 3936 ± 8 Ma, which is interpreted as an impact event. A similar age of 3941 ± 5 Ma (n = 17, MSWD = 0.89, P = 0.58) was obtained for a large zircon grain ( 430 × 340 μm in size). This grain might have crystallized in the same impact melt sheet which formed the granular zircon or the age is representative of the final extrusion of KREEP magma. The majority of zircon grains, however, occur as isolated crystal clasts within the matrix and their ages cannot be correlated with any real events (impact or magmatic) nor can the possibility be excluded that these ages represent partial resetting of the U‐Pb system.